Penyampaian Khotbah Melalui Media Live Streaming Sebagai Upaya Membangun Spiritualitas di Era Digital - Menas Misahati Hondro; Etni Grace Andi Yusuf (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
This study aims to examine the use of live streaming sermons as an effort to build congregational spirituality. This study uses a literature study method to explore the urgency of sermons in strengthening the faith and spirituality of congregations, especially in the era of digital society. Through a review of various studies, this article presents two important aspects: first, the role of sermons in shaping a deeper understanding and practice of spirituality, and second, the church's response to changes in the social and technological context, including the phenomenon of live streaming sermons. The importance of sermons in guiding, inspiring, and deepening the faith of congregations is evident in various studies that highlight their positive effects in building spirituality, both in the millennial and Z generations and in Christians in general. Meanwhile, the church's adaptation to technological challenges has given rise to the phenomenon of live streaming sermons, which offer new flexibility and accessibility in worship, but also raise considerations related to personal interaction and the sustainability of the values ​​of the spiritual community. In this context, this article emphasizes that sermons remain a vital instrument in building Christian spirituality, while adaptation to changes in the times and technology is a challenge that must be overcome wisely. Thus, sermons are not only a means of conveying spiritual messages, but also an opportunity to deepen the worship experience and expand the reach of church services in this digital era.